Pretty little mini quilts. (Lark Books, 2010)
"Pretty Little Mini Quilts" showcases the creations of 25 leading artists, many of whom have prominent online presence. The featured techniques, all explained in the basics section, include machine and hand quilting, piecing, embroidery, fusing, embellishing with beads and other materials and trapunto. All quilts are under three feet in length.